Levels of Curriculum Development in Islamic Religious Education - Syifa Ullinnas; Asmira laila; Sumiarti Sumiarti; Hamzah Irfanda (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
The curriculum is a crucial element in the education system, serving as a reference for the learning process. The curriculum development process is carried out in stages, starting from the macro level to classroom implementation. This study aims to explain the stages of curriculum development in the context of Islamic Religious Education (PAI). The methodology used was qualitative research with a literature review approach. Data were collected from books, journals, and documents related to curriculum development. The results indicate that curriculum development consists of four main levels: the macro (national) level, the institutional level, the subject level, and the operational level in the classroom. These four levels are interconnected to create effective and meaningful learning